2010
DOI: 10.1088/0004-637x/714/2/1324
|View full text |Cite
|
Sign up to set email alerts
|

2007 Outburst of 17p/Holmes: The Albedo and the Temperature of the Dust Grains

Abstract: Based on optical and infrared observations, we study the albedo and the temperature of the dust grains associated with the spectacular 2007 outburst of Jupiter-family comet 17P/Holmes. We found that the albedo at the solar phase angle ∼16 • was 0.03-0.12. While the color temperature around 3-4 μm was 360 ± 40 K, the color temperature at 12.4 μm and 24.5 μm was ∼200 K, which is consistent with that of a blackbody. We studied the equilibrium temperature of the dust grains at 2.44 AU and found that the big discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 56 publications
1
37
1
Order By: Relevance
“…It is found that the infrared spectrum of the diffuse emission can be explained by a mixture of amorphous and crystalline silicate materials as observed in most comets (Watanabe et al 2009;Reach et al 2010). Total ejecta mass was estimated to be 10 10 -10 13 kg (Montalto et al 2008;Altenhoff et al 2009;Reach et al 2010;Ishiguro et al 2010;Boissier et al 2012). More than a 2-m-thick surface layer could be blown off by the initial event although this is strongly dependent on the size distribution and maximum size of the dust par-ticles .…”
Section: P/holmes Is a Distinguished Comet Because Of Its Spectaculmentioning
confidence: 96%
See 2 more Smart Citations
“…It is found that the infrared spectrum of the diffuse emission can be explained by a mixture of amorphous and crystalline silicate materials as observed in most comets (Watanabe et al 2009;Reach et al 2010). Total ejecta mass was estimated to be 10 10 -10 13 kg (Montalto et al 2008;Altenhoff et al 2009;Reach et al 2010;Ishiguro et al 2010;Boissier et al 2012). More than a 2-m-thick surface layer could be blown off by the initial event although this is strongly dependent on the size distribution and maximum size of the dust par-ticles .…”
Section: P/holmes Is a Distinguished Comet Because Of Its Spectaculmentioning
confidence: 96%
“…In the range, we obtained i n = (5.3-6.0)×10 −10 Jy/m 2 . In contrast, the flux from the dust coma, i c that has an equivalent total cross-sectional area was derived in the manner described in Ishiguro et al (2010). We calculated the equilibrium temperature of a 1-µm-sized particle r h =2.23 AU using the optical constants of astronomical silicate (217 K), magnetite (229 K), and graphite (235 K) and derived a thermal flux at 18-µm AKARI wavelength of i c = 2.0×10 −9…”
Section: Dust Mass-loss Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Reach et al (2010) distinguished three coma components: a shell, a 'blob' of ejecta containing separate filaments and a 'core' centered on the nucleus where the shell is due to small particles while the core and blob can be explained by larger particles. Ishiguro et al (2010) estimated the lower limit of the ejected mass removed by the initial outburst for 4 · 10 10 kg (equivalent to a few meters thick surface layer of the nucleus) -presumably not only the dust mantle but also the pristine layer beneath the surface. Schleicher (2009) estimated a total amount of water ice and dust that was vaporized and emitted during four months of subsequent activity.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the huge outburst of Comet Holmes is attributed to an internal explosive source of energy in the nucleus. In the literature are considered various exothermic chemical reactions involving free radicals or pockets of volatile gas stored beneath the surface (Altenhoff et al, 2009;Ishiguro et al, 2010;Reach et al, 2010;Schleicher, 2009;Sekanina, 2008). It should be also noted, that evolution of gas pressure within cometary nuclei and mechanisms for outbursts were investigated also in relations to other comets (e.g Prialnik and Bar-Nun, 1990;Huebner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%